2006
DOI: 10.1097/00006199-200603000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Which Influence Latino Community Members to Self-Prescribe Antibiotics

Abstract: Interventions to improve antibiotic use that are focused on the formal healthcare system (e.g., clinicians, pharmacists, persons with health insurance) are unlikely to be effective with recently immigrated Latino community members. Successful interventions for this population should include targeted messages to bodega employees, community organizations, and children and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 27 publications
7
78
1
1
Order By: Relevance
“…This may be particularly worrisome in an immigrant Latino population. There is evidence that Latinos are more likely to obtain and take antibiotics without a prescription 16,29 , since many have immigrated from countries where it is common to buy antibiotics over the counter without prescription. Further, a previous study reported that antibiotics were readily available over-the-counter in small, private delis (bodegas) in upper Manhattan where many participants in this study lived, 30 and most Hispanics residing in upper Manhattan are of Dominican descent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be particularly worrisome in an immigrant Latino population. There is evidence that Latinos are more likely to obtain and take antibiotics without a prescription 16,29 , since many have immigrated from countries where it is common to buy antibiotics over the counter without prescription. Further, a previous study reported that antibiotics were readily available over-the-counter in small, private delis (bodegas) in upper Manhattan where many participants in this study lived, 30 and most Hispanics residing in upper Manhattan are of Dominican descent.…”
Section: Discussionmentioning
confidence: 99%
“…The KA survey tool has been previously used 15 and was adapted from other instruments used in previous community studies. [16][17][18] The KA survey included 57 close-ended questions assessing knowledge, attitudes, and practices about viral URI and influenza. Seven questions asked participants whether medications commonly used in clinical practice were antibiotics or not.…”
Section: Measurement Of Knowledge and Attitudesmentioning
confidence: 99%
“…It would be unrealistic to believe that patients would disregard previous experience in seeking care and treatment expectations every time they have a respiratory infection. 13,[17][18][19] Consequently, a desire for antibiotics previously used to treat respiratory infections is not a Latino-specific cultural phenomenon. However, the use of a variety of strategies, including acquiring antibiotics without a prescription from tiendas and pharmacies within the United States, does seem to be a cultural artifact of the loosely regulated sale of antibiotics in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…19 Currently, there are no published results of interventions to combat this behavior, which has significant implications for the development of antibiotic resistance and public health. 21 Education about any sort of intervention to promote the use of appropriate channels for acquiring antibiotics and to decrease inappropriate self-medication seems necessary, but a strategy of educating individuals about the differences between viruses and bacteria in the etiology of upper respiratory infections would probably not be effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation